2013
DOI: 10.1371/journal.pgen.1003517
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin and AP2 Are Required for Phagocytic Receptor-Mediated Apoptotic Cell Clearance in Caenorhabditis elegans

Abstract: Clathrin and the multi-subunit adaptor protein complex AP2 are central players in clathrin-mediated endocytosis by which the cell selectively internalizes surface materials. Here, we report the essential role of clathrin and AP2 in phagocytosis of apoptotic cells. In Caenorhabditis elegans, depletion of the clathrin heavy chain CHC-1 and individual components of AP2 led to a significant accumulation of germ cell corpses, which resulted from defects in both cell corpse engulfment and phagosome maturation requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 60 publications
(77 reference statements)
1
45
0
2
Order By: Relevance
“…Interestingly, previous studies in C. elegans have suggested that dynamin might contribute to Rab5 recruitment to phagosomes during phagocytosis of apoptotic cells (Kinchen et al, 2008). More recently, in C. elegans, dynamin has been shown to form a complex with clathrin, clathrin adaptor protein complex 2 (AP2), and LST-4 (the C. elegans homolog of mammalian proteins Snx9, Snx18 and Snx33) to promote phagosome maturation during apoptotic cell corpse clearance (Chen et al, 2013). Therefore, dynamin might have more than one function in phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies in C. elegans have suggested that dynamin might contribute to Rab5 recruitment to phagosomes during phagocytosis of apoptotic cells (Kinchen et al, 2008). More recently, in C. elegans, dynamin has been shown to form a complex with clathrin, clathrin adaptor protein complex 2 (AP2), and LST-4 (the C. elegans homolog of mammalian proteins Snx9, Snx18 and Snx33) to promote phagosome maturation during apoptotic cell corpse clearance (Chen et al, 2013). Therefore, dynamin might have more than one function in phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Subunits of the AP-1 and AP-2 complexes, as well as retromer, are found at phagosomes, and, while this may seem superficially like a case of neofunctionalization, is consistent with a role for AP-1 in phagocytosis in murine macrophages [75], and evidence for roles for both AP-2 and retromer in phagocytic clearance of apoptotically killed cells in Caenorhabditis elegans [201,202]. Therefore, many seemingly non-canonical functions of trafficking factors in E. histolytica may represent specialization common to professional phagocytic cells.…”
Section: Discussionmentioning
confidence: 64%
“…Degron-tagged reporters also allow the specific labelling of a single membrane or surface of a membrane. The close proximity of the corpse plasma membrane and the engulfing phagosome membrane make it difficult to distinguish their signals using fluorescence microscopy 26,27 , unless cells have distinct transcriptional programs, i.e. neuronal corpses engulfed by non-neuronal cells.…”
Section: Degron Reporters Reveal Plasma Membrane Topology and Dynamicsmentioning
confidence: 99%